Improving Sound Absorption Property of Polyurethane Foams by Adding Tea-Leaf Fibers - EKICI, Bulent; KENTLI, Aykut; KUCUK, Haluk (Archives of Acoustics, 2013)
The sound absorption property of polyurethane (PU) foams loaded with natural tea-leaf fibers andluffa cylindrica (LC) has been studied. The results show a significant improvement in the sound absorptionproperty parallel to an increase in the amount of tea-leaf fibers (TLF). Using luffa-cylindrica as a fillermaterial improves sound absorption properties of soft foam at all frequency ranges. Moreover, an increasein the thickness of the sample resulted in an improvement of the sound absorption property. It is pleasingto see that adding tea-leaf fibers and luffa-cylindrica to the polyurethane foam demonstrate a significantcontribution to sound absorption properties of the material and it encourages using environmental friendlyproducts as sound absorption material in further studies.